2014
DOI: 10.1007/s00359-014-0971-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of muscarinic acetylcholine receptors elevates intracellular Ca2+ concentrations in accessory lobe neurons of the chick

Abstract: Accessory lobes are protrusions located at the lateral sides of the spinal cord of chicks and it has been proposed that they play a role as a sensory organ for equilibrium during walking. We have reported that functional neurons exist in the accessory lobe. As there is histological evidence that synaptic terminals of cholinergic nerves exist near the somata of accessory lobe neurons, we examined the effects of acetylcholine on changes in intracellular Ca2+ concentrations ([Ca2+]i), as an index of cellular acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Conversely, besides neurons, ChAT expression has also been reported in other cell types such as epithelial and immune cells, and reduction in tissue acetylcholine concentration could therefore reflect changes in these cells. 22 Besides reduced acetylcholine expression in the proximal colon, we also observed a reduced sensitivity of the colonic muscle to the muscarinic agonist bethanechol. These modifications could also be due to altered expression of muscarinic receptors present on smooth muscle cells or downstream alterations of signaling pathways and effectors activated by these receptors.…”
Section: Discussionmentioning
confidence: 63%
“…Conversely, besides neurons, ChAT expression has also been reported in other cell types such as epithelial and immune cells, and reduction in tissue acetylcholine concentration could therefore reflect changes in these cells. 22 Besides reduced acetylcholine expression in the proximal colon, we also observed a reduced sensitivity of the colonic muscle to the muscarinic agonist bethanechol. These modifications could also be due to altered expression of muscarinic receptors present on smooth muscle cells or downstream alterations of signaling pathways and effectors activated by these receptors.…”
Section: Discussionmentioning
confidence: 63%
“…In the injection experiment, Ach solution was directly injected into the electrode dish using a micropipette. Ach concentration was 1 mM which is sufficient concentration to get response of membrane proteins 32 . From the result, we confirmed that the slice responded to Ach.…”
Section: Resultsmentioning
confidence: 99%